2021
DOI: 10.3390/plants10020294
|View full text |Cite
|
Sign up to set email alerts
|

Grazing Intensity Alters Leaf and Spike Photosynthesis, Transpiration, and Related Parameters of Three Grass Species on an Alpine Steppe in the Qilian Mountains

Abstract: The effect of grazing on leaf photosynthesis has been extensively studied. However, the influence of grazing on photosynthesis in other green tissues, especially spike, has remained poorly understood. This study investigated the impact of different grazing intensities (light grazing (LG), medium grazing (MG), and heavy grazing (HG)) on leaf and spike photosynthesis parameters and photosynthetic pigments of three grass species (Stipa purpurea, Achnatherum inebrians, and Leymus secalinus) on an alpine steppe in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 109 publications
(137 reference statements)
0
6
0
Order By: Relevance
“…Chla+b/Car represents a good indicator of plant stress detection and tolerance and is sensitive to photooxidative damage. Our study indicated that grazing significantly increased Chla+b/Car, suggesting that grazed trees show a lower oxidative stress intensity [43].…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Chla+b/Car represents a good indicator of plant stress detection and tolerance and is sensitive to photooxidative damage. Our study indicated that grazing significantly increased Chla+b/Car, suggesting that grazed trees show a lower oxidative stress intensity [43].…”
Section: Discussionmentioning
confidence: 51%
“…Grazed trees exhibited significantly higher chlorophyll content than ungrazed trees during spring. These results suggest that grazing stimulated total chlorophyll synthesis [43] and could induce a compensation mechanism against herbivores [40]. The trees increased the photosystem components used to promote photosynthesis efficiency by improving the transfer of electrons through the reaction centers.…”
Section: Discussionmentioning
confidence: 85%
“…Photosynthesis is a determining factor of plant productivity (Flexas & Carriquí, 2020; Li et al, 2021; Ma et al, 2021). According to a previous study on the diurnal dynamics of photosynthesis in S. breviflora , the plants showed the peak electron transfer rate, Rubisco enzyme activity, photosynthetic rate, E , G s , and the C i between 09:00 a.m. and 10:00 a.m.…”
Section: Discussionmentioning
confidence: 99%
“…There was a study that investigated the impact of different grazing intensities [light grazing (LG), medium grazing (MG), and heavy grazing (HG)] on leaf photosynthesis parameters and photosynthetic pigments of three grass species on an alpine steppe in the Qilian Mountains. Grazing had a positive effect on the leaf photosynthesis parameters of S. purpurea and L. secalinus ( Li et al., 2021 ). However, it is not clear how grazing regulates photosynthesis and light compensation.…”
Section: Discussionmentioning
confidence: 99%